Association Between the Adequacy of Preoperative Antituberculosis Treatment with Abdominal Postoperative Morbidity and Mortality on Tuberculosis Patients - El Anshori, Riza; Putranto, Agi S. (The New Ropanasuri Journal of Surgery, 2019)
Introduction. The adequacy of tuberculosis treatment before abdominal surgery is a dilemma faced by surgeons who aims for low risk of morbidity and mortality. In addition, there is no data on morbidity and mortality post abdominal operation on TB patients in RSCM and RS Persahabatan. Therefore, this research aims to show the correlation between the adequacy of preoperative TB treatment and postoperative morbidity (fistula enterocutaneous, obstruction, and surgical site infection) and mortality. Method. This study is a descriptive-analytic cross-sectional study done in Cipto Mangunkusumo Hospital dan Persahabatan Hospital using total sampling method, a total of 59 subjects with TB and had undergone abdominal operation and was admitted from January 2011 to August 2017, that fulfilled the criteria of this study. Bivariate and multivariate analysis using SPSS was done to analyze the correlation between TB treatment adequacy and postoperative morbidity and mortality. Results 46 subjects (78%) did not receive adequate preoperative TB treatment. The morbidity rate in this study is 29 subjects 49.25% with significant correlation with the adequacy of preoperative TB treatment (p = 0.030). From the three morbidities in this study (fistula enterocutaneous, obstruction, surgical site infection), only surgical site infection (SSI) has significant correlation with TB treatment adequacy (p = 0.048). There is no significant correlation with postoperative mortality (p = 0.564). Compared to elective surgery, emergency surgery has higher morbidity (OR = 1.62; 95% CI 0.58 - 4.53) and SSI (OR = 2.02; 95% CI 0.63 - 6.46) incidence. A significant difference in the incidence of SSI between clean and dirty surgery wound was found (p = 0.030). Multivariate analysis showed that both adequacy of antituberculosis treatment and surgery type are independent risk factors for morbidity (p = 0.025). Conclusion: Adequate preoperative TB treatment lowers the postoperative morbidity such as surgical site infection. There is no significant correlation between adequate preoperative TB treatment and mortality, and other morbidities such as fistula enterocutaneous and obstruction. Morbidity and SSI are more likely to happen in emergency surgery than elective surgery. Both adequacy of antituberculosis treatment and surgery type are independent risk factors for morbidity.